2016
DOI: 10.3389/fbuil.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seismic Protection Methods for Buried Fuel Pipelines Subjected to Fault Rupture

Abstract: Buried steel fuel pipelines are critical lifelines for the society and the economy but are very vulnerable to earthquake-induced ground failure. Traversing seismic areas inevitably results in several pipe-fault crossings. Fault rupture forces a buried pipeline to undergo deformations that could be substantial and heavily endanger its integrity. Due to the grave consequences of a potential pipe failure, mitigating measures are commonly applied at pipe-fault crossings to reduce the effects of a potential fault a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Other more drastic preventative measures include use of flexible joints and above-ground elevation or re-routing of a pipeline portion to avoid hazardous land zones, the latter rarely being an option due to right-of-way permissions. A more comprehensive list of such measures can be found, among others, in [126,171,172]. In [171], a comparative quantitative evaluation of alternative measures is also presented, and it is found that geotextile fabrics, pipe wall thickness increase and trench backfilling with loose soil provide rather low to moderate protection, while concrete culverts appear more effective.…”
Section: Risk Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other more drastic preventative measures include use of flexible joints and above-ground elevation or re-routing of a pipeline portion to avoid hazardous land zones, the latter rarely being an option due to right-of-way permissions. A more comprehensive list of such measures can be found, among others, in [126,171,172]. In [171], a comparative quantitative evaluation of alternative measures is also presented, and it is found that geotextile fabrics, pipe wall thickness increase and trench backfilling with loose soil provide rather low to moderate protection, while concrete culverts appear more effective.…”
Section: Risk Mitigation Strategiesmentioning
confidence: 99%
“…A more comprehensive list of such measures can be found, among others, in [126,171,172]. In [171], a comparative quantitative evaluation of alternative measures is also presented, and it is found that geotextile fabrics, pipe wall thickness increase and trench backfilling with loose soil provide rather low to moderate protection, while concrete culverts appear more effective. The effectiveness of each preventative measure reflects directly on the residual functionality following a seismic event (i.e., robustness), and implicitly has effect on the recovery time.…”
Section: Risk Mitigation Strategiesmentioning
confidence: 99%
“…The comparison of "conventional" measures presented by Gantes and Melissianos 2016;Melissianos et al 2017c;Melissianos and Gantes 2019; yields the following results for practical consideration:…”
Section: Types Of Protection Measuresmentioning
confidence: 97%
“…Qualitative discussions on protection measures are offered by Nyman et al (2008), O'Rourke and , and Karamanos et al (2017). Quantitative comparisons of measures are presented by Gantes and Melissianos (2016), Melissianos et al (2017c), Gantes (2019), and. In these studies, the authors have grouped the measures into three categories, based on the mechanism employed to achieve pipe strain reduction: pipe strengthening, soil friction reduction, and complex measures.…”
Section: Protection Measuresmentioning
confidence: 99%
“…For pipelines crossing fault belts, a combination of ground treatment, structure improvement, and seismic monitoring is generally adopted to mitigate the risk (Honegger et al, 2004). One efficient seismic protection is pipeline placement within culverts or the use of flexible joints (Gantes and Melissianos, 2016). However, the seismic design of a buried pipeline across a fault is complex and governed by many factors, such as the ground and structure conditions, fault activities, and damage mechanisms.…”
Section: Introductionmentioning
confidence: 99%